Feminization of International Migration and Transnational Household Bargaining Power Shifts: Disentangling the Underlying Migration Effect Channels - Rivera, Josel Richa Ann D (Philippine Management Review, 2023)
This study investigates the effect of migrant parent’s gender on the expenditure patterns of the household. It also attempts to disentangle the different channels underlying the effect of migration on the expenditures by applying the separate spheres bargaining framework in the context of a transnational household. Using a two-year cross-sectional dataset from the Philippines, an instrumental variable approach is used to address the endogeneity of migration by exploiting exogenous variation in the sex ratio of children in the household. Results show that spending for general, day-to-day, nondiscretionary, and demand-based expenditures such as food and health is influenced more by presence-based bargaining power while income- based bargaining power has more impact on longer term substantial expenditures like education.